Infecciones de implantes, un desafío actual para la medicina y la odontología. - Betancur, Daniel; Ulloa, Camilo; Chaparro, Alejandra; Venegas, Bernardo; Valdivia-Gandur, Iván; Beltrán, Víctor (Journal of Oral Research, 2020)
.